The prevalence of familial vesicoureteric reflux in infants with normal antenatal scans. (9th June 2022) - Singhal, Nidhi; Gopal, Milan; Ali, Alaa; McGlade, Fiona; Ahmed, Imran; Harkensee, Christian; Gittins, Nicola; Senasi, Ramdas; Peace, Richard; Athiraman, Naveen; Tse, Yincent
Abstract: Aim: To determine the prevalence of familial vesicoureteric reflux (VUR) by studying the outcomes of screening in a contemporary cohort of newborns with normal antenatal kidney scans. Methods: A review of screening outcomes in newborns with a first degree relative with VUR, normal antenatal scans and no prior urine infections between 2014–2019 at three maternity units in the North East of England was conducted. Imaging consisted of micturating cystourethrogram (MCUG) in all and renal tract ultrasound scan (RUS) routinely in two units and by clinician preference in one unit. Results: At a median age of 59 days, 265 infants underwent MCUG. High‐grade VUR (Grades 3–5) was detected in 13 (4.9%) and low‐grade VUR (Grades 1–2) in 24 (9.1%). In the 152 infants who had a RUS, abnormalities were detected in 21 (13.8%). An abnormal postnatal RUS has a low positive predictive value (14.3%) for high‐grade VUR, but a normal RUS has a high negative predictive value (95.4%). Conclusion: Compared to historical cohorts from two decades ago, the yield from familial VUR screening is low and unjustifiable in the setting of normal antenatal anomaly scans.